A REVIEW OF THE GENERAL ASPECTS OF REPRODUCTION OF A THREATENED FRESH WATER FISHSPECIES IN BENIN: PARACHANNA OBSCURA (GÜNTER, 1861) - Azon, Mahunan Tobias Césaire; SOSSOUKPE, EDMOND; Vodounnou, D.S. Juste Vital; CHIKOU, Antoine; Mensah, Guy Apollinaire; Fiogbe, Emile Didier (My University, 2020)
Parachanna obscura is a fresh water fish belonging to Channidae family that is recognized as snakehead fish. Its first sexual maturity height is 17.5 cm TL in females and 23.4 cm TL in males. Sexual dimorphism based on observation of the genital papilla is difficult to recognize. The fish species is carnivorous with rapid growth rate. For further evaluation of its aquaculture potential in Benin Republic, the current study aims to make a review on the reproductive aspect of P. obscura. Its resistance, rapid growth and high economic and nutritional values represent important potential for aquaculture because it is highly appreciated by the West African population in general. The natural stock of P. obscurais currently threatened to disappearance in Benin due to fishing pressures that lead to overexploitation. A successful rearing of P. obscura in controlled medium could ensure not only the preservation and improvement of natural stocks but also the production of food fish for sustainable aquaculture
Keywords: Parachanna obscura; aquaculture; reproduction; sexual dimorphism.